2020
DOI: 10.1016/j.msea.2020.139287
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dynamic plastic deformation on the microstructure and mechanical properties of an Al–Zn–Mg alloy

Abstract: A supersaturated Al-Zn-Mg alloy was processed by dynamic plastic deformation (DPD) using a Split-Hopkinson pressure bar (SHPB) facility with strain range from 0.5 to 1.5 and then subjected to compressive testing at strain rates of 1×10 -3 ~ 4×10 3 s -1 . The results show that there is concurrent occurrence of grain refinement, increase in dislocation density and precipitation of fine precipitates in different morphologies during DPD at strain over 1. This enhances the yield strength of the Al alloy after DPD o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…On the contrary, the relatively high 10 revolutions led to the dissolution of this fragmented intermetallic compounds of the η phase into the Al matrix in the HPT-10 sample due to the high deformation energy. The low activation energy (Q d ) value characterizing the dissolution (endothermic) reactions in the HPT-10 sample is caused mainly by the dissolution of the low fraction of η phase, which remained at grain boundaries because the dissolution of precipitates inside the grains is less pronounced [28]. Following the dissolution reaction at the first endothermic process, the formation/re-formation of precipitates occurred as presented by the exothermic reaction peak in the DSC line profile.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, the relatively high 10 revolutions led to the dissolution of this fragmented intermetallic compounds of the η phase into the Al matrix in the HPT-10 sample due to the high deformation energy. The low activation energy (Q d ) value characterizing the dissolution (endothermic) reactions in the HPT-10 sample is caused mainly by the dissolution of the low fraction of η phase, which remained at grain boundaries because the dissolution of precipitates inside the grains is less pronounced [28]. Following the dissolution reaction at the first endothermic process, the formation/re-formation of precipitates occurred as presented by the exothermic reaction peak in the DSC line profile.…”
Section: Discussionmentioning
confidence: 99%
“…Despite extensive investigations [26][27][28][29][30], the effect of the shear strain in a wide range of deformation imposed in HPT processes on the microstructure and on the subsequent mechanical properties of several AlZnMg alloys has not been clarified in detail.…”
Section: Introductionmentioning
confidence: 99%
“…However, the SRS of the DPD-0.75-450 sample is more sensitive than DPD-0.75 and this is because of the presence of more κ-carbides precipitated during the post-DPD aging where this leads to a significant reduction in 𝑙𝑙 * in Eq. ( 10) which offsets the effect of dislocation recovery and grain coarsening and thereby leads to an increment in SRS [24,48].…”
Section: Effect Of Strain Rate On Compression Behaviormentioning
confidence: 99%
“…There are several reports available documenting the microstructure evolution and mechanical properties improvement of different materials after DPD processing, such as pure Cu [9][10][11][12][13], Ti [14][15][16], aluminum alloys [1,3,[17][18][19][20][21][22][23][24] and steels [2,4,[25][26][27][28][29][30]. Some of these studies showed that steels were significantly strengthened by grain refinement after DPD processing [4,26].…”
Section: Introductionmentioning
confidence: 99%
“…Deformation of alloy needed enough time or else boundaries of dislocation cell couldn't have attained equilibrium and disorder each dislocation cell in microstructure as well as temperature which was transformed the dislocations in to sub-grains as laminar layers. Afifi et al 100 reported a Split-Hopkinson pressure bar (SHPB) facility with strain range used to measure densified dislocations during dynamic plastic deformation (DPD) of supersaturated Al-Zn-Mg alloy. The strain rate was increased after repeated passes of DPD and the dislocations density also increased at different strain rates moreover grain refinement combined with dislocations transformed as fine precipitates.…”
Section: Influence Of Dislocations On Al Alloys Propertiesmentioning
confidence: 99%